Microstructural Integrity of the Hippocampus During Childhood: Relations With Age and Source Memory - Callow, Daniel D.; Canada, Kelsey L.; Riggins, Tracy (Frontiers in Psychology, 2020)
The hippocampus is a brain structure known to be important for memory. However, studies examining relations between hippocampal volume and memory across development yield mixed results. This may be due in part to the fact that volume is a coarser measure of hippocampal composition. Studies have begun to examine measures of diffusion, which capture characteristics of the microstructure of the hippocampus, and thus may provide additional information about the integrity of the underlying neural circuits. The present study applied this approach to a developmental period characterized by dramatic changes in both hippocampal microstructure and memory behavior – early childhood. Specifically, measures of hippocampal microstructural integrity were related to age and source memory performance in 93 children aged 4- to 8-years. Results revealed significant negative associations between hippocampal mean diffusivity and both age and memory, even after controlling for differences in hippocampal volume. These results suggest hippocampal diffusion may provide additional, independent information about hippocampal integrity compared to volume, particularly during early childhood when important developmental changes have been proposed.